Striving with Global Stress on a Local Level: Has the COVID-19 Pandemic Changed the Relationship between People and Nature? - Gunko Ruslan; Rapeli Lauri; Karell Patrik (MDPI, 2022)
The COVID-19 pandemic had harsh consequences on human health and society across the globe. In addition to health effects, the pandemic also influenced people's values, concerns, and ethics due to lockdowns and general limitations in societal activities. In this study, we examined changes in the relationship between people and nature caused by COVID-associated stress, as well as its consequences on life quality, by comparing questionnaire-based survey data before and during the pandemic. We found that the pandemic had positive effects on individual respondents' relationships with nature. Respondents who were more affected by the pandemic rated their life quality lower than those who were less affected. In accordance, the pandemic had a negative effect on people's life quality, especially for people living in areas where the environment (coastal water quality) was in poor condition. Our results support the prediction that environmental quality may buffer against global stress and improve societal wellbeing.